Virtual Non-Contrast CT Using Dual-Energy Spectral CT: Feasibility of Coronary Artery Calcium Scoring - Song, Inyoung (Korean J Radiol, 2016)
OBJECTIVE: To evaluate the feasibility of coronary artery calcium scoring based on three virtual noncontrast-enhanced (VNC) images derived from single-source spectral dual-energy CT (DECT) as compared with true noncontrast-enhanced (TNC) images. MATERIALS AND METHODS: This prospective study was conducted with the approval of our Institutional Review Board. Ninety-seven patients underwent noncontrast CT followed by contrast-enhanced chest CT using single-source spectral DECT. Iodine eliminated VNC images were reconstructed using two kinds of 2-material decomposition algorithms (material density iodine-water pair [MDW], material density iodine-calcium pair [MDC]) and a material suppressed algorithm (material suppressed iodine [MSI]). Two readers independently quantified calcium on VNC and TNC images. The Spearman correlation coefficient test and Bland-Altman method were used for statistical analyses. RESULTS: Coronary artery calcium scores from all three VNC images showed excellent correlation with those from the TNC images (Spearman's correlation coefficient [ρ] = 0.94, 0.88, and 0.89 for MDW, MDC, and MSI, respectively; p < 0.001 for all pairs). Measured coronary calcium volumes from VNC images also correlated well with those from TNC images (ρ = 0.92, 0.87, and 0.91 for MDW, MDC, and MSI, respectively; p < 0.001 for all pairs). Among the three VNC images, coronary calcium from MDW correlated best with that from TNC. The coronary artery calcium scores and volumes were significantly lower from the VNC images than from the TNC images (p < 0.001 for all pairs). CONCLUSION: The use of VNC images from contrast-enhanced CT using dual-energy material decomposition/suppression is feasible for coronary calcium scoring. The absolute value from VNC tends to be smaller than that from TNC.